Long‐term outcomes in patients treated with proton therapy for localized prostate cancer. (6th September 2017) - Takagi, Masaru; Demizu, Yusuke; Terashima, Kazuki; Fujii, Osamu; Jin, Dongcun; Niwa, Yasue; Daimon, Takashi; Murakami, Masao; Fuwa, Nobukazu; Okimoto, Tomoaki
Abstract: The aim of this retrospective study was to report long‐term clinical outcomes in patients treated with proton therapy (PT) for localized prostate cancer. Between 2001 and 2014, 1375 consecutive patients were treated with PT. Patients were classified into prognostic risk groups based on the National Comprehensive Cancer Network criteria. Freedom from biochemical relapse (FFBR), cancer‐specific survival (CSS) and incidence of late gastrointestinal (GI)/genitourinary (GU) toxicities were calculated. Multivariate analysis was performed to identify clinical prognostic factors for FFBR and late toxicities. The median follow‐up period was 70 months (range, 4–145 months). In total, 99% of patients received 74 Gy (relative biologic effectiveness [RBE]); 56% of patients received neoadjuvant androgen deprivation therapy. For the low‐, intermediate‐, high‐, and very high‐risk groups, 5‐year FFBR was 99% (95% confidence intervals [CI], 96–100%), 91% (95% CI, 88–93%), 86% (95% CI, 82–89%), and 66% (95% CI, 53–76%), respectively, and 5‐year CSS was 100% (95% CI, 100–100%), 100% (95% CI, 100–100%), 99% (95% CI, 97–100%), and 95% (95% CI, 94–98%), respectively. Patient age, T classification, Gleason score, prostate‐specific antigen, and percentage of positive cores were significant prognostic factors for FFBR. Grade 2 or higher GI and GU toxicities were 3.9% and 2.0%. Patient age was a prognostic factor for both late GI and GU toxicities. This study represents the largest cohort of patients treated with PT for localized prostate cancer, with the longest follow‐up to date. Our results demonstrate that the biochemical control of PT is favorable particularly for high‐ and very high‐risk patients with lower late genitourinary toxicity and indicates the necessity of considering patient age in the treatment protocols. Abstract : Proton therapy for localized prostate cancer demonstrates favorable biochemical control particularly for high‐ and very high‐risk patients and a lower incidence of late genitourinary toxicity. Our findings indicate the necessity of considering patient age in the treatment protocols.